Prevalence of Muscular Sarcosporidiosis in Slaughtered Domestic Pigs in Perak, Peninsular Malaysia - Fazly Ann Zainalabidin; Muhamad Syamsul Naim Noorazmi; Wan Normaziah Wan Omar Bakri; Geethamalar Sathaya; Mohd Iswadi Ismail (Tropical Life Sciences Research, 2017)
Sarcosporidiosis is a disease caused by intracellular protozoan parasites, namely, Sarcocystis spp. In pigs, three species of Sarcocystis spp. have been recognised, including Sarcocystis meischeriana, Sarcocystis porcifelis and Sarcocystis suihominis. The aim of this study is to determine the prevalence of muscular sarcosporidiosis in pigs using the pepsin digestion technique. A total of 150 fresh heart, oesophagus and thigh muscle samples from 50 Yorkshire and Landrace pigs were collected from two local abattoirs in Perak from May to August 2014. All the fresh muscle samples were thoroughly examined for macrocyst-forming Sarcocystis spp. and processed using the peptic digestion technique to detect bradyzoites. The results from the muscle samples showed that 58% (29 out of 50) of the pigs were positive for Sarcocystis spp. These findings highlight the importance of implementing stringent measures for screening pigs in abattoirs for Sarcocystis spp. infection because this infection in pigs is a public health concern. Sarkosporidiosis adalah penyakit yang disebabkan oleh parasit protozoa intraselular iaitu Sarcocystis spp. Pada khinzir, tiga spesis Sarcocystis spp. telah dikenalpasti antaranya Sarcocystis meischeriana, Sarcocystis porcifelis dan Sarcocystis suihominis. Tujuan kajian ini adalah untuk menentukan prevalens sarkosporidiosis otot pada khinzir dengan menggunakan teknik penghadaman peptik. Sebanyak 150 sampel segar otot jantung, esofagus dan paha daripada 50 khinzir jenis Yorkshire dan Landrace telah dikumpulkan dari dua buah tempat sembelihan tempatan di Perak mulai bulan Mei hingga Ogos 2014. Kesemua sampel segar tersebut diperiksa secara kasar untuk mengesan pembentukan-makrosis Sarcocystis spp. dan seterusnya diproses secara teknik penghadaman peptik bagi mengesan kehadiran bradizoit. Hasil yang diperolehi menunjukkan 58% (29 daripada 50) khinzir adalah positif terhadap Sarcocystis spp. Penemuan ini menggambarkan kepentingan untuk melaksanakan langkah-langkah yang ketat dalam pemeriksaan khinzir-khinzir di rumah sembelihan terhadap infeksi Sarcocystis spp. kerana kepentingannya terhadap kesihatan awam.